Dark materials: Pre-Columbian black lithic carvings from St Vincent and the wider Caribbean - Brock, F; Ostapkowicz, J; Collinson, ME; Bull, ID; Dyer, C; Lane, DW; Domoney, K; Uden, J (Elsevier, 2020)
A small number of pre-Columbian black lithic carvings have been found at archaeological sites across the Caribbean, as well as in parts of neighbouring mainland South America. The identity of the material used to create these artefacts is often unknown, but suggestions include lignite, wood, petrified wood, manja(c)k, jet (or ‘jet-like’ materials) and hardened asphalt. These identifications are often historical and lacking any scientific basis, and as such can be unreliable. However, identification of the material has the potential to inform on the source of the carving and thereby pre-Columbian trade routes within the circum-Caribbean region. Four analytical techniques (reflectance microscopy, FTIR, Py-GC/MS, x-ray fluorescence) were applied to samples taken from two carvings found on St Vincent and five comparative materials. Both artefacts were found to be most likely carved from cannel coal, indicating that they originated in South America (where cannel coal is found extensively in locations in Colombia and Venezuela), as the material is not found within the Caribbean region.